2012
DOI: 10.1108/17465261211219822
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial orientations of business students and entrepreneurs

Abstract: PurposeThe purpose of this paper is to explain the implications of different entrepreneurial orientations on business start‐up and development challenges.Design/methodology/approachThis research reflects surveys of 1,075 experienced entrepreneurs and business and entrepreneurship students in Estonia during the years 2005‐2010. An additional method is action learning and reflections of training focused on recognising new business opportunities during the economic crises.FindingsCombinations of co‐creative and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 23 publications
(26 reference statements)
0
31
0
2
Order By: Relevance
“…Santandreu-Mascarell, Garzon, and Knorr (2013) revealed that one way entrepreneurs contribute to economic development is through innovation involving the growth of new products, new processes, new supply sources, new market exploitation, and the development of new ways to organize business. In addition, there is another important feature of an innovator's competence, which is to know whether markets are ready for commercializing their innovative solutions (Elenurm, 2012). Literature on entrepreneurial intention also shows the positive effect of innovativeness on entrepreneurial attitude (Robinson et al, 1991).…”
Section: Innovativenessmentioning
confidence: 99%
“…Santandreu-Mascarell, Garzon, and Knorr (2013) revealed that one way entrepreneurs contribute to economic development is through innovation involving the growth of new products, new processes, new supply sources, new market exploitation, and the development of new ways to organize business. In addition, there is another important feature of an innovator's competence, which is to know whether markets are ready for commercializing their innovative solutions (Elenurm, 2012). Literature on entrepreneurial intention also shows the positive effect of innovativeness on entrepreneurial attitude (Robinson et al, 1991).…”
Section: Innovativenessmentioning
confidence: 99%
“…Entrepreneurship is largely rooted in the research of Mintzberg (1973), while the scales are mainly credited to Khandwalla (1977) and Lumpkin and Dess (1996). Some examples of studies on entrepreneurship orientation in the Baltic area are those of Elenurm andAlas (2009) andElenurm (2012).…”
Section: Discussionmentioning
confidence: 99%
“…In support of teaching entrepreneurial skills Gürol and Atsan (2006), not too surprisingly, recognise entrepreneurial traits to be higher in entrepreneurially inclined students when compared to their entrepreneurially non-inclined students' counterpart. They have higher risk-taking propensity, internal locus of control, higher innovativeness and higher needs for achievements (Elenurm, 2012;Iredale, 2010, 2014;Short et al, 2010). Meanwhile, many academics and scholars support innovation and entrepreneurial studies as a means to improving a nations prosperity (Hynes, 1996;Hytti and O'Gorman, 2004;Rae, 2007;Draycott and Rae, 2011;Beynon et al, 2014).…”
Section: Teaching Entrepreneurship In Higher Educationmentioning
confidence: 99%